Investment Patterns in Singapore's Central Provident Fund System - KOH, Benedict S. K. (Institutional Knowledge at Singapore Management University, 2008)
Rising elderly life expectancies imply the need to accumulate sufficient savings for retirement. This paper investigates the role of recent changes in the investment menu of the Singaporean Central Provident Fund (CPF) system. Our research explores the investment patterns of CPF participants and articulates their implications for policymakers. We find that most investors use their money for housing purchase and default the remainder to the CPF investment pool. The bulk of non-housing saving sits in bank accounts paying a low return. A fraction of workers does elect outside investment products, with high-income earners and males taking more risk than low-income earners and females. Since workers who default their money to the CPF fund receive a guaranteed 2.5% return on the Ordinary Account and 4% on the Special Account, hurdle rates for money market and equity funds are substantial. These high hurdle rates help explain why few CPF account holders invest outside the default government investment pool, though inertia probably explains why many employees let their funds sit in bank accounts earning low interest rates. More attention could be devoted to lowering fund expenses and commissions, including the myriad of fees, expenses, loads, and wrap charges; it might also be beneficial to streamline and rationalize the investment menu offered to participants. [PUBLICATION ABSTRACT]